2015
DOI: 10.9725/kstle.2015.31.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Tribology Characteristics in 200 μm of Hexagonal Array Dimple Pattern

Abstract: − This study investigates the effects of a pattern of 200 µm dimples in a hexagonal array on tribological characteristics. A textured surface might reduce the friction coefficient and wear caused by third-body abrasion and thus improve the tribological performance. There are three friction conditions based on the Stribeck curve: boundary friction, mixed friction, and fluid friction conditions. In this experiment, we investigate the friction characteristics by carrying out the friction tests at sliding speeds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Surface texturing to create square-patterned dimples or pores has been reported to reduce the coefficient of friction due to lubricant retention. In the previous research, the hexagonal pattern of 200 µm dimple has reported by Choi et al [1], nevertheless the surface texturing method has been studied since 1940's. Surface texturing can be performed by chemical, mechanical or varied method to create marking in the surface [2].…”
Section: Introductionmentioning
confidence: 97%
“…Surface texturing to create square-patterned dimples or pores has been reported to reduce the coefficient of friction due to lubricant retention. In the previous research, the hexagonal pattern of 200 µm dimple has reported by Choi et al [1], nevertheless the surface texturing method has been studied since 1940's. Surface texturing can be performed by chemical, mechanical or varied method to create marking in the surface [2].…”
Section: Introductionmentioning
confidence: 97%